Reflecting on the Delivery of a Longitudinal Coping Intervention Amongst Junior National Netball Players - Devonport, Tracey J. (Asist Group, 2009)
Recent research suggests that appropriately-tailored interventions can assist adolescents enhance their coping skills (Frydenberg and Lewis, 2004). The present paper reflects upon the delivery of a longitudinal coping intervention utilized by junior national netball players. Reflection is focused on issues such as the rationale for the intervention, operational issues surrounding the delivery and management of the work. It is also focused on interpersonal issues relating to intervention implementation. We contend that being explicit about developmental and applied processes may enable theoretically sound and efficacious practices to be identified. In addition, unpacking operational issues related to delivery may assist applied sport and exercise psychologists in the development of related work.